2005
DOI: 10.1002/jmri.20407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of normal fatty replacement of the thymus with chemical‐shift MR imaging for identification of the normal thymus

Abstract: Purpose: To clarify the influences of age and gender on normal fatty replacement of the thymus in childhood, adolescence, and early adulthood using chemical-shift MRI. Materials and Methods:A total of 95 normal subjects (52 males and 43 females, mean age ϭ 15.6 years, range ϭ 7-25 years) who underwent chemical-shift MRI of the thymus were assessed prospectively. Signal intensity loss (SIL) of the thymus was determined by dividing the thymus/ muscle ratio on the opposed-phase image by that on the in-phase image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 18 publications
(29 reference statements)
0
39
0
1
Order By: Relevance
“…For children and adolescents, this finding is consistent with a previous study that evaluated the fatty replacement of the normal thymus with chemical-shift MRI in 95 healthy volunteers. 20 Those investigators found that chemical-shift MRI can detect physiological fatty infiltration of the normal thymus in all subjects ≥16 years, in half of adolescents aged [10][11][12][13][14][15][16] years, but in none <10 years, although a microscopic and gradually increasing amount of fat in the normal thymus exists from birth. 20 In addition, a recent report described a case of non-suppressing normal thymus in a 21-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For children and adolescents, this finding is consistent with a previous study that evaluated the fatty replacement of the normal thymus with chemical-shift MRI in 95 healthy volunteers. 20 Those investigators found that chemical-shift MRI can detect physiological fatty infiltration of the normal thymus in all subjects ≥16 years, in half of adolescents aged [10][11][12][13][14][15][16] years, but in none <10 years, although a microscopic and gradually increasing amount of fat in the normal thymus exists from birth. 20 In addition, a recent report described a case of non-suppressing normal thymus in a 21-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…20 Those investigators found that chemical-shift MRI can detect physiological fatty infiltration of the normal thymus in all subjects ≥16 years, in half of adolescents aged [10][11][12][13][14][15][16] years, but in none <10 years, although a microscopic and gradually increasing amount of fat in the normal thymus exists from birth. 20 In addition, a recent report described a case of non-suppressing normal thymus in a 21-year-old woman. 23 Thus, similarly to the normal thymus, cases of nonsuppressing TLH at chemical-shift MRI may also occur in patients with MG, even in early adulthood, as seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently reported that chemical shift MRI is useful for characterizing the normal thymus by detecting the intravoxel fat tissue within the thymus. Chemical shift MRI can depict physiological fatty replacement of the normal thymus in nearly 50% of subjects age 11-15 years, and in nearly 100% of those over 15 years (5) (Fig. 1).…”
Section: Normal Thymusmentioning
confidence: 99%